Dinamika Urusan Konkuren Antar Pemerintah Pusat Dan Pemerintah Daerah Dalam Sistem Desentralisasi - Mesy Azmiza Azhar (Lex Renaissance, 2022)
This study analyzes the shifts in decentralization in Indonesia from time to time. The decentralization system itself has a crucial role in developing regional needs. However, it had triggered abuse by the Chiefs of the Region. This was responed by amendment to Law No. 22 of 1999 on Regional Government with Law No. 32 of 2004 on Regional Government. However, the present law has brought about a shift in decentralization which ssentially accommodates the broad authority of the regional government in the typology of regional autonomy to fade. This was strengthened when the enactment of Law No. 23 of 2014 which divides concurrent powers that should belong to the regional government to the central government. This study uses normative research methods, as well as statutory approach. The results of the study concluded that: (1) there is a decrease in the meaning of decentralization because concurrent affairs are centralized in Law No. 23 of 2014 concerning Regional Government. (2) Weakening the role of the DPD thereby reducing decentralization. Therefore, this study recommends: (1) returning the concurrent affairs absolutely to the regions; (2) strengthening the role of the DPD to in return strengthening the decentralization and accommodating the regional needs.Key Words: Decentralization; concurrent affairs; central government; local government AbstrakPenelitian ini menganalisis pergeseran desentralisasi di Indonesia dari masa ke masa. Sistem desentralisasi sendiri memiliki peran penting dalam pengembangan kebutuhan daerah. Namun, sempat memicu penyalahgunaan oleh kepala daerah. Hal itu ditangkis melalui perubahan Undang-Undang No. 22 Tahun 1999 tentang Pemerintah Daerah dengan Undang-Undang No. 32 Tahun 2004 tentang Pemerintah Daerah. Hanya saja, melalui Undang-Undang tersebut justru terjadi pergeseran desentralisasi yang pada dasarnya mengakomodasi kewenangan pemerintah daerah secara luas dalam tipologi otonomi daerah, menjadi semakin pudar. Hal ini menguat ketika lahirnya Undang-Undang No. 23 Tahun 2014 yang membagi kekuasan konkuren yang seharusnya menjadi wewenang daerah kepada pemerintah pusat. Penelitian ini menggunakan metode penelitian normatif, serta pendekatan perundang-undangan. Hasil penelitian menyimpulkan: (1) ada penurunan makna desentralisasi karena urusan konkuren yang sentralistis pada UU No. 23 Tahun 2014 tentang Pemerintahan Daerah. (2) Pelemahan peran DPD sehingga turut mereduksi desentralisasi. Oleh karena itu penelitian ini merekomendasikan: (1) mengembalikan urusan konkuren secara mutlak kepada daerah; (2) memperkuat peran DPD untuk memperkuat desentralisasi dan mengakomodasi kebutuhan daerah.Kata-kata Kunci: Desentralisasi; urusan konkuren, pemerintah pusat; pemerintah daerah